2015
DOI: 10.9734/bmrj/2015/18250
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Detection of Extended Spectrum Beta-Lactamase and Carbapenemases Produced by Klebsiella spp Isolated from Three Referrals Hospitals in Yaounde, Cameroon

Abstract: Aims:The main objective of this study was to determine the resistance phenotype of β-lactamines by Klebsiella in three hospitals in Yaoundé. Study Design: A cross-sectional descriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The interplay of the genetic disposition of K. pneumoniae makes it better organized for mobilizing resistant genes from other drug resistant bacteria in the environment or in animal/human microbial communities. This further explains why K. pneumoniae is always the predominant species as was the case in an earlier study (19). Such information is fundamental for shaping effective routine analysis of clinical specimens.…”
Section: Discussionsupporting
confidence: 58%
“…The interplay of the genetic disposition of K. pneumoniae makes it better organized for mobilizing resistant genes from other drug resistant bacteria in the environment or in animal/human microbial communities. This further explains why K. pneumoniae is always the predominant species as was the case in an earlier study (19). Such information is fundamental for shaping effective routine analysis of clinical specimens.…”
Section: Discussionsupporting
confidence: 58%
“…This result is different from results reported by Betbeui and collaborators in 2015 from three referral hospitals in Yaounde. The study reported lower rates of resistance for the cephalosporins [16]. Thus there has been an increase over time in resistance to cephalosporins.…”
Section: Discussionmentioning
confidence: 78%
“…Thirty seven Klebsiella isolates were identified using the API 20E identification system. Among the species isolated Klebsiella pneumoniae was the most prevalent with 54.1%, followed by Klebsiella rhinoscleromatis 18.9%, Klebsiella ozaenae 16.2% and Klebsiella oxytoca, 10.8% as shown on Figure 1 below. Klebsiella species were most isolated from pus 24.3%, urinary catheter and urine with a frequency of 21.6% each and isolated least from venous catheter 5.4% as shown on Table 1.…”
Section: Resultsmentioning
confidence: 91%
“…The low rate of CP-GNB clinical samples is similar to that reported by a study in Chad (2.5%), 4 but is less than in Cameroon (Central Africa; 11.11%) and Senegal (West Africa; 5.1%). 22,23 Conversely, it is more than that in Burkina Faso (West Africa; 0.9%). 24 This low rate in Gabon could be explained by the high cost of carbapenems, which reduces the risk of excessive use, and therefore promotes the appearance of resistance.…”
Section: Discussionmentioning
confidence: 96%